Violin plots of performance metrics across all testers. - Stefan Saverimuttu (20882325) (2025)
Recall, precision, and F1-score (as labelled) distributions (y-axis), for each tested clinicopathologic finding (x-axis), across all testers of the application for extraction of necropsy data from the Wildbase Pathology Register, DEE.